2009
DOI: 10.1175/2009jtecha1235.1
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Bias Estimation of Historical HIRS Using IASI Observations for Improved Fundamental Climate Data Records

Abstract: A prerequisite for climate change detection from satellites is that the measurements from a series of historical satellites must be consistent and ideally made traceable to the International System of Units (SI). Unfortunately, this requirement is not met for the 14 High Resolution Infrared Radiation Sounders (HIRS) on the historical NOAA satellites, because the instrument was developed for weather forecasts and lacks accuracy and consistency across satellites. It is well known that for HIRS, differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…GSICS aims to ensure the comparability of satellite measurements performed from different instruments (sounders/imagers, infrared/microwave) and platforms, to interpret the differences, and to link the measurements to absolute references and standards. Intercomparisons have been performed with HIRS, AIRS, the Spinning Enhanced Visible and Infrared Imager (SEVIRI), and the Advanced Along-Track Scanning Radiometer (AATSR) using simultaneous nadir overpass (SNO) methods or double-difference (DD) methods (e.g., Cao et al 2009;Illingworth et al 2009;Hewison 2008a,b;Tobin 2008;Wang and Cao 2008). Biases are also characterized via the study of residuals between IASI observations and simulations based on radiative transfer code and collocated radiosoundings (Blumstein et al 2010).…”
Section: Independent Radiance Calibration and Validation Studiesmentioning
confidence: 99%
“…GSICS aims to ensure the comparability of satellite measurements performed from different instruments (sounders/imagers, infrared/microwave) and platforms, to interpret the differences, and to link the measurements to absolute references and standards. Intercomparisons have been performed with HIRS, AIRS, the Spinning Enhanced Visible and Infrared Imager (SEVIRI), and the Advanced Along-Track Scanning Radiometer (AATSR) using simultaneous nadir overpass (SNO) methods or double-difference (DD) methods (e.g., Cao et al 2009;Illingworth et al 2009;Hewison 2008a,b;Tobin 2008;Wang and Cao 2008). Biases are also characterized via the study of residuals between IASI observations and simulations based on radiative transfer code and collocated radiosoundings (Blumstein et al 2010).…”
Section: Independent Radiance Calibration and Validation Studiesmentioning
confidence: 99%
“…The factors that may cause the systematic biases but are not related to AIRS and IASI are the calibration MARCH 2010 W A N G E T A L .…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…Statistical data reduction reduces random uncertainty caused by variations in local weather conditions (a necessity in this case), but propagate, amplify, and even distort systematic uncertainty across space-time scales (Stubenrauch et al 2013). With radiometric differences shown to be at or below the climate accuracy requirement of 0.1 K for most conditions, they concluded that data from these systems have the potential to create fundamental climate data records of radiances (e.g., Cao et al 2009;Gunshor et al 2009;Wang and Cao 2008;Wang et al 2009). Toward this end, we processed the AIRS, IASI, and CrIS radiance measurement records in the exact same manner to avoid the introduction of algorithm-related discrepancies.…”
Section: Resultsmentioning
confidence: 99%